Reduction aortoplasty and external wrapping for moderately sized tubular ascending aortic aneurysm with concomitant operations - ARSAN, SİNAN (ELSEVIER SCIENCE INC, 2004)
Background. Replacement of the ascending aorta with a prosthetic graft is the preferred surgical procedure for an ascending aortic aneurysm. The choice of external wrapping of the aorta is a simple, fast, and effective method for moderately sized ascending aortic aneurysms with concomitant operations. In this study, we present the midterm results of 62 patients undergoing reduction aortoplasty with external wrapping and different cardiac procedures. Methods. The study group consisted of 48 male and 14 female patients with a mean age of 59.3 +/- 6.0 years. Measurement of the ascending aorta diameters was obtained at three points: before surgery, during the early postoperative period, and during the follow-up. The mean preoperative aortic diameter was 52.7 +/- 0.5 mm. In all patients, the ascending aortic aneurysm was repaired by reduction aortoplasty with external wrapping. Results. Mean follow-up time was 39.6 +/- 18.0 months. There was only one mortality (1.6%) as a result of septic multiple-organ failure and no major surgical complications in the 30-day postoperative period. Reduction aortoplasty of the ascending aorta with external wrapping resulted in a significant reduction of the ascending aorta in all patients (p = 0.000). There was an increase in the mean aortic diameter during the follow-up period (p = 0.000). Although this increase was statistically significant, all measurements of the follow-up period were still within normal range. Conclusions. External wrapping of the aorta offers excellent results with very low mortality and morbidity, and it can be regarded as a safe and effective method for the treatment of ascending aortic aneurysm in selected patients. However, the patients should be carefully monitored for redilatation after the procedure. (C) 2004 by The Society of Thoracic Surgeons.
Keywords: VALVE DISEASE; REPLACEMENT; RESECTION; REPAIR